Spiritual connection in daily life : sixteen little questions that can make a big difference - Underwood, Lynn (Templeton Press, 2013)
How often do you find moments of deep peace and satisfaction in your day-to-day life? How often does connection with other people, the divine, or nature make you feel more alive? How often are you touched by a sense of awe-inspiring beauty, compassionate love, or pure joy? For many of us, these kinds of experiences tend to be fleeting and all too rare. Fortunately, new research is suggesting that a regular practice of paying attention to experiences like these can help any of us find them more often and cultivate richer, deeper, and more satisfying lives. In Spiri.